2017
DOI: 10.1371/journal.pone.0186798
|View full text |Cite|
|
Sign up to set email alerts
|

Early postnatal vocalizations predict sociability and spatial memory in C57BL/6J mice: Individual differences in behavioral traits emerge early in development

Abstract: The understanding of individual diversity and its link to brain functions is a fundamental issue in neurobiology. Studies in mice have mainly focused on the investigation of behavior traits in adulthood, whereas longitudinal analyses are largely uninvestigated. Here we have conducted systematic behavior tests in individual mice (C57BL6/J, male), comparing phenotypes at early postnatal stages and in adulthood. Each animal showed different scores in individual behavior tests. However, we observed an inverse corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Our results contribute to previous reports integrating isolation calls into the study of the development of individual differences in behavioural traits (Hudson et al, ; Yoshizaki, Koike, Kimura, & Osumi, ). For example, pups’ isolation calls have been shown to be linked with sociability, spatial memory and emotionality in adults (laboratory rats: Brunelli & Hofer, ; laboratory mice: Winslow et al, ; Yoshizaki et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Our results contribute to previous reports integrating isolation calls into the study of the development of individual differences in behavioural traits (Hudson et al, ; Yoshizaki, Koike, Kimura, & Osumi, ). For example, pups’ isolation calls have been shown to be linked with sociability, spatial memory and emotionality in adults (laboratory rats: Brunelli & Hofer, ; laboratory mice: Winslow et al, ; Yoshizaki et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Since one objective of our research was to examine whether HFD-induced obesity was a risk factor for psychiatric disorders and cognitive impairment, we analyzed the correlation between body weight and behavioral traits, according to a previous paper [35]. We unexpectedly found that HFD-induced body weight was not associated with either hyperlocomotion or anhedonia-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Significant individual differences in USVs have been observed in mice and rats, as well as in the individual variation in immune responses . Particularly interesting in the context of this article is the work of Bronson and colleagues, who using a poly I:C MIA model in rats reported that individual differences in the maternal response to immune challenge influence the behavioral response in the offspring …”
Section: Common Traits Between Immunity and Vocalizationmentioning
confidence: 91%